MENDORONG RESES PARISIPATIF MASUK DALAM TATA TERTIB DPRD KOTA PAREPARE - ibrahim Fattah (FAKULTAS HUKUM UM PAREPARE, 2019)
The recess is regulated in the DPRD rules but does not regulate the method of community involvement so that many recess results do not reveal the problems faced by the community and consequently the solution is not found to later become a development activity that is budgeted annually through the APBD. The purpose of this paper is to find out the right strategy related to revising the DPRD Regulations governing the recess of DPRD members. To find out the factors that influence the implementation of recess of DPRD members. To find out the results of implementing Participatory Recess for DPRD members and the community. The research method that I use in this study is socio-normative consisting of normative and sociological research. The approach to legislation (statue approach) is to review a number of legislative rules relating to the recess of DPRD members. The results of the research are conducting a strategy, namely; Identify to Publish the process of implementing participatory recesses through media newspapers and online media. The influencing factors are; 1) the availability of Human Resources that are national regulations on Information Technology, Integrity, consistent attitudes and behaviors, media publications, and Civil Society Organization (CSO) Partitions. The results of the implementation of Participatory Recess for DPRD members and the community in the City of Parepare are more maximal